2019
DOI: 10.1109/access.2019.2957435
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Joining Strategies in Cognitive Radio Networks Under Primary User Emulation Attacks

Abstract: Cognitive radio (CR) networks allow secondary users (SUs) to access and use the spectrum opportunistically. However, some misbehavior users mislead SUs to evacuate the spectrum by launching a primary user emulation attack (PUEA), which is a denial of service (DoS) attack. During the service of an SU, the arrival of the malicious misbehavior users (MMUs) will force the SU under service to leave the system. Another type of attack, different from the MMU, refers to the selfish misbehavior users (SMUs) who launch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The results shown in Figs. 14,15,16,17,18,19,20,21 have been plotted to accomplish the same. Please note that all the results are for the final values of the considered algorithms.…”
Section: Discussion On the Performance Of The Exhaustive Search Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shown in Figs. 14,15,16,17,18,19,20,21 have been plotted to accomplish the same. Please note that all the results are for the final values of the considered algorithms.…”
Section: Discussion On the Performance Of The Exhaustive Search Mechanismmentioning
confidence: 99%
“…In [13], a spectrum access function based framework has been proposed for the SU to access the PU spectrum in a manner which reduces it's probability of miss-detection. The authors in [14] perform a game theory based study of a system facing PUEAs. It is shown that CSS works better than the individual SU systems for PUEA avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Wang [21] developed the queueing-gametheory for analyzing the behavior of the SU. Here, the CRN was analyzed under two types of misbehavior users such as Malicious Misbehavior Users (MMUs) and Selfish Misbehavior Users (SMUs).…”
Section: Literature Surveymentioning
confidence: 99%
“…Therefore, ensuring security is of paramount importance to the successful deployment of cognitive radio networks. More explicitly, jamming attacks, Denial of Service (DoS) attacks [11], Primary User Emulation Attack (PUEA) [12]- [14], Spectrum Sensing Data Falsification Attack (SSDFA) [15], exploitation of common control channel security [16] and collaborative jamming [17] are well known attacks in cognitive radio networks. However, our major concern is to combat jamming attacks in cognitive radio networks.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the Q value is the estimation of the expected sum of the discounted payoff [8]. Hence, an SU can consider the Q value in a bimatrix game at stage k as the expected sum of the discounted payoffs given in (14). Given the Q function Q(s k , a k ), the SU can find the value of the game from:…”
mentioning
confidence: 99%